Optimization of Extraction Parameters for Antioxidant and Total Phenolic Content of Ficus carica L. Latex from White Genoa Cultivar - Shahinuzzaman, M.; Yaakob, Zahira; Sani, Norrakiah Abdullah; Akhtar, Parul; Islam, Md. Zahidul; Mimi, Mst. Afsana; Shamsudin, Shamsul Akmal (Asian Journal of Chemistry, 2019)
In this study, the extraction parameters for antioxidant activity and total phenolic content of Ficus carica L. latex from White Genoa cultivar were optimized using response surface methodology (RSM). Effect of temperature, extraction time and solvent concentration for maceration extraction were investigated. The antioxidant activity was determined with DPPH (1,1-diphenyl-2-picrylhydrazyl) assay and expressed as percent of inhibition. Total phenolic content (TPC) was determined with Folin-Ciocalteu assay and expressed as μg GAE/mL. The optimum points that maximize the DPPH inhibition are 32 °C temperature, 31.50 min extraction time and 65 % ethanol. The optimum points for TPC are 32 °C temperature, 37.50 min extraction time and 70 % ethanol. The predicted DPPH inhibition and TPC at these predicted points are 67.08 % and 313.811 μg GAE/mL respectively. In this model, the F value (26.03 and 20.96), R-Squared value (0.9591 and 0.9497) and signal to noise ratio (13.431 and 12.799) are reasonable to fit the model.